Variations in Cochlear Size of Cochlear Implant Candidates - Devira Zahara; Rima Diana Dewi; Askaroellah Aboet; Fikri Mirza Putranto; Netty Delvrita Lubis; Taufik Ashar (International Archives of Otorhinolaryngology, 2019)
Abstract